Understanding Texts in English a Challenge for Future Professionals - López Medina Consuelo (Universidad Nacional de Colombia, 2001)
This project was conducted in the Fundación Universitaria San Martín with night accounting students who were coursing sixth semester. They were taking 3rd level of English. The purpose of the study was to improve reading comprehension through the use of some reading strategies. A group of 6 students was chosen because of their low level and difficulties in understanding texts in English. Data collection was conducted using questionnaires, teacher's observation and teacher's diary. Results showed that students mostly liked to read topics related to their programs, despite their lack of vocabulary, and they improved reading comprehension through the use of adequate reading strategies, avoiding the overuse of translation.